2017
DOI: 10.1002/2017je005352
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Localized Source of the Argon in the Lunar Exosphere

Abstract: We perform the first tests of various proposed explanations for observed features of the Moon's argon exosphere, including models of the following: spatially varying surface interactions; a source that reflects the lunar near‐surface potassium distribution; and temporally varying cold trap areas. Measurements from the Lunar Atmosphere and Dust Environment Explorer (LADEE) and the Lunar Atmosphere Composition Experiment (LACE) are used to test whether these models can reproduce the data. The spatially varying s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Modeling by Prem et al () shows that surface roughness can have this effect by providing cold surfaces at high latitudes that can act as temporary reservoirs for molecules near the poles. A semiannual oscillation in argon observed by the Lunar Atmosphere and Dust Environment Explorer spacecraft has been linked to sequestration in transitory seasonal cold traps (Hodges & Mahaffy, ; Kegerreis et al, ). Hodges () notes that the magnitude of seasonal oscillation implies that significant areas of high‐energy adsorption sites on soil grains in the seasonal cold traps are free of water molecules, placing a restrictive upper bound on the exospheric transport of water.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling by Prem et al () shows that surface roughness can have this effect by providing cold surfaces at high latitudes that can act as temporary reservoirs for molecules near the poles. A semiannual oscillation in argon observed by the Lunar Atmosphere and Dust Environment Explorer spacecraft has been linked to sequestration in transitory seasonal cold traps (Hodges & Mahaffy, ; Kegerreis et al, ). Hodges () notes that the magnitude of seasonal oscillation implies that significant areas of high‐energy adsorption sites on soil grains in the seasonal cold traps are free of water molecules, placing a restrictive upper bound on the exospheric transport of water.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that an alternative scenario is proposed by Kegerreis et al () that argon‐40 originates in, and leaks out of, a near‐surface deposit of K‐rich material that underlies the western maria. Since there is no evidence of seismic wave attenuation that would signal a semimolten state in this region, and since Kegerreis et al do not discuss why argon should escape from subsolidus rock, their theory will be ignored here.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are temporarily sequestered at depth (where they arrived after diffusing downwards during the lunar night) and are released much later (mid-day). This mechanism, proposed by Kegerreis et al (2017), could explain the slight time delay from dawn of the peak 40 Ar exospheric density recorded by LACE and LADEE without requiring the high activation energy all over the lunar surface proposed by Hodges and Mahaffy (2016). Interestingly, a similar mechanism (the "thermal pump") has been proposed for other species -most notably waterat the Moon (Schörghofer and Taylor 2007;Schörghofer and Aharonson 2014), Mercury (Vasavada et al 1999), and Mars (Mellon and Jakosky 1993).…”
Section: Argonmentioning
confidence: 71%
“…As discussed in Sect. 2.2, Kegerreis et al (2017) showed that this process, by which argon atoms migrate downwards during the night and are released during the day later than dawn, can explain the half-an-hour delay in the sunrise exospheric density bulge measured by both LACE and LADEE.…”
Section: Simulationsmentioning
confidence: 95%
See 1 more Smart Citation